The evaluation of cytotoxic effects, antimicrobial activity, antioxidant activity and combination effect of Viscum rotundifolium and Mystroxylon aethiopicum - Malada, Patience M.; Mogashoa, Mary M.; Masoko, Peter (Elsevier B.V. on behalf of SAAB., 2022)
The high rate of infections and antibiotic resistance causes serious difficulties to the healthcare system. Therefore there is a need to develop new antimicrobial agents with little side effects. The aim of the study was to investigate the impact of different solvents on extraction yields, antioxidant and antimicrobial potential, cytotoxic and combination effects of different leaf extracts of Viscum rotundifolium (parasite) and Mystroxylon aethiopicum (host). The leaves of V. rotundifolium and M. aethiopicum were collected, dried and ground into fine powder. The powdered plant leaves were extracted using solvents of varying polarity namely: hexane, ethyl acetate, acetone, methanol and water. The standard chemical tests were used to screen the phyto-constituents present in the plant leaves. The antioxidant activity was determined using 2, 2-Diphenyl-1-pycrylhydryzyl (DPPH) assay and ferric reducing power assay. The antimicrobial activity of extracts was tested against bacterial strains using serial micro-dilution assay. The cytotoxic effects of the plant extracts were determined using cell viability assay. Methanol was the best extractant compared to the other extractants with the percentage yield of 31% (M. aethiopicum) and 27% (V. rotundifolium). The occurrence of phyto-constituents (terpernoids, flavonoids, phlabotannins, tannins steroids and cardiac-glycosides, alkaloids and saponins) was similar in both plant leaves. The quantitative DPPH and ferric reducing power assay revealed the presence of antioxidant activity in all plant species. The minimum inhibitory concentration (MIC) values ranged from 0.31 mg/mL to 2.5 mg/mL. The combination of hexane, ethyl acetate and acetone extracts showed synergistic effects in inhibiting the growth of S. aureus. The cytotoxicity study reveals that plants are nontoxic to human cells. The study demonstrated that the extracts of the selected plants have antibacterial potential against the tested microorganisms which may be ascribed to the phytochemicals present in the plants.
Journal article published in South African Journal of Botany Volume 147, (2022), 790-798
Keywords: Antibiotic; Healthcare system; Antimicrobial; Antioxidan; Plant leaves; Antineoplastic antibiotics; Peroxiredoxins; Viscum; Antibiotics -- Side effects